Depression, Anxiety And Stress In Women With Breast Cancer: Effect Of A 4-Week Self Management Intervention - Loh, S.Y.; Tan, F.L.; Xavier, M. (2009)
Objective: This study examined the relationship between depression, anxiety and stress before and after a patient self-management intervention in a cohort of women newly diagnosed with breast cancer. Methods: A clinical trial on women diagnosed with breast cancer was conducted at University Malaya Medical Centre. The experimental block underwent a 4-week self management program, followed by the control block who underwent usual care. Participants were assessed on their levels of depression, anxiety and stress at baseline (T1), at 4 weeks (T2) and at 8 weeks (T3) after the intervention. Analyses of variances on the repeated measures were conducted to examine the differences between the two groups. Results: There were significant differences in the change-scores between the experimental and control groups at post test and at follow up. Levels of depression, anxiety and stress generally decreased significantly in the experimental groups but either maintained or increase in the control group. Significantly lower stress was also found in women with higher level of self-reported physical activity than women with low physical activity. Conclusion: The depression, anxiety and stress level of women with breast cancer can be ameliorated with a 4 week self management intervention. Women with higher physical activity also show significantly lower stress. Intervention should consider factors that ameliorate distress level of women with breast cancer so that they can better go through adjuvant therapy.